IMAGE QUALITY AND ARTIFACTS ON OPTICAL COHERENCE TOMOGRAPHY ANGIOGRAPHY: Comparison of Pathologic and Paired Fellow Eyes in 65 Patients With Unilateral Choroidal Melanoma Treated With Plaque Radiotherapy. Issue 9 (September 2017) - Say, Emil A. T.; Ferenczy, Sandor; Magrath, George N.; Samara, Wasim A.; Khoo, Chloe T. L.; Shields, Carol L.
Abstract : Purpose: To study image quality and artifacts seen on optical coherence tomography angiography (OCTA). Methods: Sixty-five consecutive patients with unilateral posterior uveal melanoma treated with plaque radiotherapy had OCTA during follow-up. Optical coherence tomography angiography was performed on both the affected and fellow eye. Signal strength and frequency of image artifacts on en face images were compared between affected and fellow eyes. Results: A total of 130 eyes in 65 patients were analyzed, the mean age at time of OCTA was 55 years (median: 56, range: 12–81 years), and 39 (39/65, 60%) were female. Majority of tumors were located in the choroid (62/65, 95%) and extramacular (55/65, 85%). The mean distance to the foveola was 4 mm (median: 3, range: 0–18 mm) and optic nerve was 4 mm (median: 4, range: 0–16 mm). Optical coherence tomography angiography was performed at a mean 46 months after plaque radiotherapy. Most patients had a history of radiation maculopathy or papillopathy in the treated eye at the time of OCTA (46/65, 71%). Overall, 95 eyes (95/130, 73%) had at least one significant artifact on OCTA. The most common major artifacts were loss of focus (71/130, 55%), broad (>5 pixels width and >4 lines) blink lines (48/130, 37%), motion artifact (34/130, 26%), specular dot (33/130, 25%), and edge duplication (10/130, 8%). Statistically, eyes treated with plaque radiotherapy (affected vs. fellow eye) were more likely to have at least one major OCTA artifact (92 vs. 54%, P < 0.001) and, specifically, loss of focus was more frequent (78 vs. 31%, P < 0.001). Multivariate analysis found decreased visual acuity significantly associated with higher incidence of broad blink lines ( P = 0.0166) and loss of signal ( P < 0.0001), whereas male sex was associated with increased loss of signal ( P = 0.0015), and distance to the foveola was related to edge duplication ( P = 0.0119). Conclusion: Image artifacts on OCTA are commonly encountered and appear to be more frequent in eyes with pathology and poor visual acuity. Recognition of these artifacts might help improve image interpretation and decision making. Abstract : Image quality and artifacts are often seen on optical coherence tomography angiography (OCTA). In eyes with unilateral choroidal melanomas treated with plaque radiotherapy, artifacts are more frequent compared with the contralateral fellow eyes.